The environmental education in the theatrical appreciation-creation workshops of the elementary school - Gladys M. Pina Betancourt; Mavel Moré Estupiñán (ADIDE Federación, 2014)
The present article deals with the methodological and theoretical basis concerning the Theatrical Appreciation- Creation Workshops of the Elementary School and their possibilities for the attention to the Environmental Education. It is remarked, as a result of the systematization of the theory and the practice, and a system didactic recommendations that contribute to the attention of the Environmental Education in the teaching and learning process of theses workshops.